2020
DOI: 10.1186/s12961-020-00553-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of contextualisation in enhancing non-communicable disease programmes and policy implementation to achieve health for all

Abstract: The September 2019 United Nations' High-Level Meeting renewed political commitments to invest in universal health coverage by strengthening health systems, programmes and policies to achieve 'health for all'. This Political Declaration is relevant to addressing the increasing global burden of non-communicable diseases, but how can evidence-based programmes and policies be meaningfully implemented and integrated into local contexts? In this Commentary, we describe how the process of contextualisation and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As such, this review highlights the limited translational research evaluating the health impacts of community-based, supervised group exercise interventions for Indigenous populations with T2D. Furthermore, in support of current recommendations, this review determined that to best facilitate the development of robust, feasible, and culturally safe evidence in this domain, interventions should be adequately contextualised to culture through consistently strong Indigenous governance and community engagement [ 37 , 38 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, this review highlights the limited translational research evaluating the health impacts of community-based, supervised group exercise interventions for Indigenous populations with T2D. Furthermore, in support of current recommendations, this review determined that to best facilitate the development of robust, feasible, and culturally safe evidence in this domain, interventions should be adequately contextualised to culture through consistently strong Indigenous governance and community engagement [ 37 , 38 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…With consideration of the small number of included studies, this review found that community-based exercise can improve glycaemic control [ 12 ], anthropometric measures [ 10 , 12 ], blood lipids [ 12 ], haemodynamic measures [ 10 ], patient activation [ 12 ], and quality of life [ 10 ] in Indigenous peoples with T2D [ 17 , 30 , 31 ]. However, upon comparing the two featured interventions [ 10 , 11 , 12 ], these adaptations appear to be largely dependent on successful cultural contextualisation of the intervention and subsequently, greater participation in the planned intervention [ 37 , 38 , 50 , 51 , 52 , 53 , 54 ]. Shah et al [ 12 ] demonstrated that biomedical outcomes, including glycaemic control, can be improved with group walking and aerobic exercise programmes as part of a holistic lifestyle intervention, including education and individualised nutrition advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they have to be tailored to the national and cultural context and the available resources. 31 Screening for vascular risk, individual focused motivational education, and motivation for a better adherence to medications provided as polypills can be performed by community health workers (CHWs), trained volunteers from stroke support organizations or medical professionals. CHWs can be facilitators and function as peer support as well as a link to the health and social services system.…”
Section: Chances and Challengesmentioning
confidence: 99%
“…A careful assessment of contextual factors and human behavior is essential when implementing population health strategies, such as dietary salt reduction to reduce the intake of excessive sodium, which is the top-ranked dietary risk factor associated with cardiovascular diseases. 1 , 2 A significant number of strokes are caused by high blood pressure due to overconsumption of sodium. 3 , 4 There has been substantial evidence from randomized clinical trials showing that reduced sodium intake leads to a decrease in blood pressure.…”
Section: Introductionmentioning
confidence: 99%